STRATEGY TO INCREASE CUSTOMER INTEREST IN GOLD PAWN PRODUCTS AT PT. BANK ACEH SYARIAH LHOKSEUMAWE BRANCH - Hamdiah; Likdanawati; Khairina AR; Sutriani; Sofatun Nisa (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2024)
This report presents the Strategy for Increasing Customer Interest in Gold Pawn Products at PT. Bank Aceh Syariah Lhokseumawe Branch. Gold pawning is a form of loan where customers provide gold jewelry as collateral in exchange for cash. One of the products that many customers are interested in is gold pawning financing where gold pawning products have a high estimated value and low deposit fees with a fast, safe and secure process. The purpose of this report is to find out the strategy to increase interest, obstacles and solutions to gold pawning. The strategy carried out is to carry out an effective marketing campaign, provide clear information, and increase trust and transparency, education and financial literacy regarding obstacles in the strategy of customer interest in pawn gold. It is important to align the strategy with the target market and needs of potential customers in Lhokseumawe. By implementing this strategy, PT Bank Aceh Syariah Lhokseumawe Branch can overcome obstacles and increase customer interest in community gold pawn services.